Electrochemical characterization of hexamethylguanidinium bis(fluorosulfonyl)imide [HMG][FSI] based electrolyte and its application in sodium metal batteries. (1st January 2023) - Biernacka, Karolina; Sun, Ju; Makhlooghiazad, Faezeh; Balkis, Ali; Gunathilaka, Isuru E; O'Dell, Luke A; Mestres, Montserrat Galceran; Howlett, Patrick C; Pringle, Jennifer M; Forsyth, Maria
Abstract: With the increasing energy demand for both electronic portable devices and energy storage for fluctuating renewable energy sources, there is a strong need for alternatives beyond lithium batteries. Sodium batteries have been attracting great attention recently due to the abundance and low supply cost of the raw materials. However, they require highly conductive, safe and electrochemically stable electrolytes in order to enable their practical realization. In this work we present the promising physicochemical properties of the electrolyte based on hexamethylguanidinium bis(fluorosulfonyl)imide [FSI] at a sodium concentration of 25 mol% NaFSI. The liquid-state electrolyte supports stable Na plating and stripping at 1 h polarization times at 0.5 mA cm −2 current density in a Na symmetrical coin cell at 50 °C, maintaining a low polarization potential of ≈45 mV throughout 160 cycles. Moreover, this electrolyte is characterized by relatively high Na-ion transference number of 0.36 ± 0.03 at 50 °C. A long cycle life of 300 cycles with 285 mAh g −1 is achieved in a half cell set up with hard carbon. The solid-electrolyte interphase layer on the anode, which contributes to this high capacity, is investigated by x-ray photoelectron spectroscopy and solid-state nuclear magnetic resonance spectroscopy. The long-term cycling performance of Na|NaFePO4 cell is also demonstrated with a high specific capacity of 106 mAh g −1 and 80% capacity retention after 110 cycles.